2005
DOI: 10.1002/path.1860
|View full text |Cite
|
Sign up to set email alerts
|

ILK over‐expression in human colon cancer progression correlates with activation of β‐catenin, down‐regulation of E‐cadherin and activation of the Akt–FKHR pathway

Abstract: Integrin-linked kinase (ILK) has been implicated in the development and progression of several human malignancies. However, the role of ILK in human colon cancer progression is not well established, neither have its possible in vivo downstream effectors in the disease been identified. We studied, by immunohistochemistry, ILK, beta-catenin, E-cadherin, p-Akt and p-FKHR protein expression in 125 primary colon carcinomas and 45 corresponding lymph node metastases. ILK was expressed in 98.4% of the primary tumours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
73
2
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 39 publications
14
73
2
7
Order By: Relevance
“…10 In the in vivo studies using human cancer tissues, the expression of pFOXO1A has been correlated with an unfavorable outcome in acute myeloid leukemia 11 as well as tumor progression and metastasis in colon cancer. 12 In contrast, no significant correlation has been noted between pFOXO1A and any of the tumor characteristics of breast cancer.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…10 In the in vivo studies using human cancer tissues, the expression of pFOXO1A has been correlated with an unfavorable outcome in acute myeloid leukemia 11 as well as tumor progression and metastasis in colon cancer. 12 In contrast, no significant correlation has been noted between pFOXO1A and any of the tumor characteristics of breast cancer.…”
mentioning
confidence: 84%
“…Our results disagree with other studies, which reported that the expression of pFOXO1A is associated with an unfavorable outcome in acute myeloid leukemia 11 or with the advanced stage of colon cancer. 12 Thus, the biological significance of the expression of pFOXO1A in the cancer appears to vary depending on the cancer cell type.…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin is one prominent adhesion molecule that forms the E-cadherin-catenin complex which plays a role in epithelial cell-cell adhesion and differentiation (38), in particular serving as a potent invasion/tumor suppressor of breast cancer (39). Previous studies indicated that the downregulation of E-cadherin was relevant to several pathways including the integrin-linked kinase (ILK) signaling pathway (40,41). The ILK signaling pathway was one prominent enrichment pathway in breast cancer, and may play an important role in hormonal cancer progression (42).…”
Section: Discussionmentioning
confidence: 99%
“…A role for ILK in tumor progression is suggested by the observation that ILK expression correlates with high tumor grade and poor prognosis in a variety of human tumors (Chung et al, 1998;Graff et al, 2001;Marotta et al, 2001;Ahmed et al, 2003;Dai et al, 2003). In some cases, such as in human colon cancer, the upregulation of ILK protein levels corresponds to an increase in Akt phosphorylation (Bravou et al, 2006).…”
Section: Integrin-mediated Activation Of Pi3k Pathwaymentioning
confidence: 99%